DNA EVIDENCE IN SOUTH AFRICA: FALLACIES AND THE FUTURE - R Kirby (Obiter, 2022)
DNA profiling evidence has become an important part of criminal proceedings in South Africa over the last decade. However, it is important to realize that DNA profiling evidence is not infallible. South African legislation and case law on DNA profiling evidence are limited. In this article, South African case law, as well as applicable legislation relating to the issue, is reviewed, followed by a discussion of relevant legislation and case law in other jurisdictions such as England, Canada and Australia. This will hopefully provide a framework for the South African legislative and the courts in dealing with DNA profiling evidence.